# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 9 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-9 y^{\prime \prime }+27 y^{\prime }-27 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-9 y^{\prime \prime }+27 y^{\prime }-27 y = {\mathrm e}^{3 x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+24 y^{\prime \prime }-32 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-9 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-10 y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-24 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }+7 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}25 y^{\prime \prime }-10 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime }-24 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+29 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+18 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-34 y^{\prime \prime }+225 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-81 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-18 y^{\prime \prime }+81 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-8 y^{\prime \prime }+37 y^{\prime }-50 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-9 y^{\prime \prime }+31 y^{\prime }-39 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+2 y^{\prime \prime }+4 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+10 y^{\prime \prime }+18 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+26 y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+9 y^{\prime \prime }+9 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+216 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-3 y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+13 y^{\prime \prime }+36 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-2 y^{\prime \prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime \prime \prime }+15 y^{\prime \prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+16 y^{\prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+16 y^{\prime \prime \prime }+64 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 24 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-8 y = 8 x^{2}-3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 36
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -6 \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = 7 \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 169 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = {\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = -18 \,{\mathrm e}^{4 x}+14 \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-10 y = 35 \,{\mathrm e}^{5 x}+12 \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 52 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 27 \,{\mathrm e}^{6 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-5 y = 30 \,{\mathrm e}^{-4 x}
\] |
✓ |
✓ |
|